(3CMdGe cHjQIs (3JMajR faSc CfJ haQjbc HGSJNOGe Mde hGVM ddMjGI (B= Dreaming big : Energizing yourself and your team with a crystal clear life dreams - (3Hjjd, HhHs; (3ShjJS, Hhds; (3ecJHI LQjQs ((3GdQjGVs (3ecJHI LQjQs, 2016)
(3jSGYO GdcJGH Ydj JMOjO Mde MjGJc, hJLQHI eSJhj LOjO JeGeG ef GdWGbI GdWHjYjI, jDcO dc GdcJGH Ydj Cf eY hLhO Mde hGVM, JSJjbX hCfJ eaYe HGdCed,(B.(3hJhGLI GdJMOjGJ HUQGeI hYbdjI EjLGHjI, CjVG jDcO GdcJGH Cf Mde MjGJc CcHQ ef Cf jSJhYHI YeQ hGMO bUjQ, Ch CcHQ ef Cf jMbbI TNU HeaQOg(B. (3dPdc jYdec gPG GdcJGH cjajI Jchjf aQjb jTGQc Mdecs
(3GdeMJhjGJ (B: (3GdNWhI GdChdj, GcJTGa Mdec (B-- (3GdNWhI GdKGfjI, JMSjf Mdec (B-- (3GdNWhI GdKGdKI, YT Mdec (B-- (3GdNWhI GdQGHYI, JYdje aQjb Yedc Cf jMde (B-- (3GdNWhI GdNGeSI, JTLjY aQjb Yedcs
"(3MOO Mde MjGJc hLQH eSJhj LOjOG ef GdWGbI GdWHjYjI(B"s
1 12 13
Keywords: (3GdMceIs; (3GdYdGbGJ GdEfSGfjIs; (3GdYed GdLeGYjs; (3GdbjGOI GdEOGQjIs; (3GdfLGM GdTNUjs; (3GdfLGMs